2023
DOI: 10.1021/acs.joc.3c01810
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to Quinone-Fused 5-Substituted-1,4-Benzodiazepine Scaffolds from Azidoquinones with/without [1,2]-Azide-Nitrogen Migration: Mechanistic Insights

Ashokkumar Krishnan,
Sriraghavan Kamaraj

Abstract: Seven-membered nitrogen heterocycles have a strong influence in drug discovery due to their inherent 3D character, which allows the ability to explore a vast conformational space with a biological target. Notably, the privileged 1,4-benzodiazepine scaffold is dominant in treating the central nervous system due to its binding affinity with the GABAA receptor. Herein, we report a protocol for the transformation of azidoquinones to p-quinone fused 5-substituted-1,4-benzodiazepines (p-QBZDs) from InCl3-catalyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Very recently, Kamaraj et al [28] discovered a InCl 3 -catalyzed intermolecular tandem cycloannulation of azidoquinones with amines and aldehydes, furnishing p-quinone fused 5-substituted-1,4-benzodiazepines (p-QBZDs) (Scheme 14). The reaction proceeded via the intermediacy of 2,3-bridged-2H-azirine followed by regiospecific addition of an amine to C=N/ring opening/cyclization to deliver p-QBZD with 1,2-azide-nitrogen migration.…”
Section: Rearrangement Of Vinyl Azide To 2h-azirinementioning
confidence: 99%
“…Very recently, Kamaraj et al [28] discovered a InCl 3 -catalyzed intermolecular tandem cycloannulation of azidoquinones with amines and aldehydes, furnishing p-quinone fused 5-substituted-1,4-benzodiazepines (p-QBZDs) (Scheme 14). The reaction proceeded via the intermediacy of 2,3-bridged-2H-azirine followed by regiospecific addition of an amine to C=N/ring opening/cyclization to deliver p-QBZD with 1,2-azide-nitrogen migration.…”
Section: Rearrangement Of Vinyl Azide To 2h-azirinementioning
confidence: 99%
“…In 2023, Krishnan and Kamaraj devised a three-component reaction of quinone azides 82 , aromatic amines 83 and aldehydes 84 for the construction of quinone-fused benzodiazepines 85 . 88 The main feature of this reaction includes 1,2-azide-nitrogen migration, as illustrated in the mechanism (Scheme 25). The InCl 3 -catalyzed tandem intermolecular cyclo-annulation reaction proceeds via the formation of bridged aziridine B (through the extrusion of N 2 from A ).…”
Section: Synthesis Of Fused Frameworkmentioning
confidence: 99%
“…12 Hence, a new class of BZDs with a broad spectrum of bioactivities with minimal adverse effects is highly desirable and is evidenced in the last two decades by the continuous flow of publications/patents, ∼43 990 hits, and ∼5186 results for clinical trials in “PubMed.” While attempting the total synthesis of Calothrixin A/B, we have encountered a serendipitous transformation of azido- p -quinones to p -quinone fused 5-substituted-1,4-benzodiazepines ( p -QBZDs) from InCl 3 -catalyzed intermolecular tandem cycloannulation of azido- p -quinones with amines and aldehydes. 13 Also, we have demonstrated that the electron-donor–acceptor (EDA) complex formation between azido- p -quinones and InCl 3 is crucial in determining the reaction pathway. In the absence of EDA complex formation, the reaction proceeds via the intermediacy of 2,3-bridged-2 H -azirine followed by regiospecific addition of an amine to CN/ring opening/cyclization to deliver p -QBZD with 1,2-azide-nitrogen migration.…”
Section: Introductionmentioning
confidence: 99%
“…Though this straightforward transformation of azido- p -quinones to structurally diversified p -quinone fused 5-substituted-1,4-benzodiazepine scaffolds compatible with various azido- p -quinones, it has certain undesired limitations like substrate-dependent yield, multiple reaction pathways and unavoidable secondary reactions (Scheme 1B). 13 To date, there are only two reports on the analogous p -quinone fused 1,4-benzodiazepines with limited substrate scope, regioselectivity issues and difficulties in accessing the required intermediates (Scheme 1C). In 2007, Reiner et al reported 14 the synthesis of N -aryl-5-aryl/alkyl substituted-1,4-naphthoquino-benzodiazepines from symmetrically/unsymmetrically substituted 2,3-bis(anilino)-1,4-naphthoquinone with aromatic/aliphatic aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation